lncRNA cytoskeleton regulator RNA (CYTOR): Diverse functions in metabolism, inflammation and tumorigenesis, and potential applications in precision oncology - Chunlin Ou; Xiaoyun He; Yong Liu; Xin Zhang (Genes and Diseases, 2023)
Long non-coding RNAs (lncRNAs) are a novel class of non-coding RNA (ncRNA), that have been studied extensively in the field of tumor research in recent years. In the case of tumor-associated lncRNAs, lncRNA cytoskeleton regulator RNA (CYTOR) displays extensive functions in tumorigenesis, including invasion, metastasis, malignant proliferation, glycolysis, and inflammatory response. Moreover, the dysregulation of CYTOR is closely related to clinicopathological characteristics, such as tumor stage, lymph node metastasis and infiltration, and poor prognosis of tumor patients. In this review, we provide a novel strategy to summarize the biological functions and clinical value of CYTOR in tumors through an overview of the literature combined with gene set enrichment analysis. A deeper understanding of the role of CYTOR in tumorigenesis may provide new diagnostic, prognostic and therapeutic markers for human tumors.